Relação lisina digestível: proteína digestível em rações para tilápias-do-nilo - Goncalves, Giovani Sampaio; Pezzato, Luiz Edivaldo; Barros, Margarida Maria; Tachibana, Leonardo; Santa Rosa, Maria Julia [UNESP]; Guimaraes, Igo Gomes [UNESP] (Revista Brasileira Zootecnia Brazilian Journal Animal Sci, 2009)
This study was carried out to determine the best digestible protein/digestible lysine ratio that should be present in feed fed to Nile tilapias. Two hundred and sixteen tilapias (11.0 +/- 0.43g) were distributed in 36 fish tanks (205 L) at a density of 6 fish/tank. Twelve feeds were formulated with three different digestible protein (DP) levels 22.0; 26.0 and 30.0% (based on digestible amino acids) and four different lysine percentages of 4.5; 6.0; 7.5 or 9.0% in relation to digestible protein. The fish were fed ad libtum during a 60-day period. There was significant effect of the digestible protein and digestible lysine ratio on weight gain, because the increase in lysine levels in feeds with 26 and 30% DP promoted linear increase in this parameter. The best values for feed conversion were obtained at the levels 26 and 30% DP that increased the daily consumption of digestible protein. The lysine level caused a linear reduction in feed conversion and linear increase in the protein efficiency rate. The results suggested that the 26% DP level might be used in ration to feed Nile tilapia juveniles; however, these should contain digestible amino acids and the digestible lysine/digestible protein ratio should be 6.0%. However, for levels higher than 26% DP, a maximum digestible lysine level of 7.5% DP improved weight gain for the species.
Digestible lysine/digestible protein ratio in diets for Nile tilapia
Keywords: amino acids; ideal protein; lysine; nutrition; Oreochromis niloticus